Thermodynamic consistency of low pressure equilibrium data of water + congener mixtures using a versatile equation of state - Faúndez, Claudio A. (2016)
A general thermodynamic consistency test is applied to analyze phase equilibrium data (TPxy data) for binary water + congener mixtures found in alcoholic distillation processes. The congeners, substances that are present at very low concentration in a must, considered in this study are: acetic acid, acetaldehyde, ethyl acetate, furfural, methanol, 1-propanol, methyl acetate and 2-butanol.  The thermodynamic test combines the Peng–Robinson equation of state modified by Kwak and Mansoori for correlating phase-equilibrium data and the Gibbs–Duhem equation to check for consistency. The test is applied to analyze twenty five isothermal P-x-y data of water+congener mixtures obtained from the literature. Of the 25 sets of data, 18 are found to be thermodynamically inconsistent. In several cases, the results are in agreement with information from the literature in which these same systems are considered to be thermodynamically inconsistent using a test that uses activity coefficients for the liquid phase.